(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2011)
Aerospace investigation methods in the first place are known as methods of remote sounding of earth surface. At decoding the remote data of ground water occurrence and distribution conditions, it is advisable to distinguish the following hydrodynamic zones: zone of intense water cycle (upper floor); zone of difficult water cycle (middle floor); zone of highly difficult or absent water cycle (lower floor).